The Influence of Workload and Work Motivation on the Performance of Teachers - SOLANIA, NIÑA; COÑADO, EDWIN; PAGUTA, MARK JOSEPH; VENTURA, RAZELIZA; ARNADO, ALVIC (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Given the nature of the teacher’s job, it is expected that they have many workloads, both teaching-related and other functions. Literature suggests that too much workload for teachers may affect their teaching performance. In addition, work motivation is another factor affecting teachers’ performance, with studies suggesting that those who have high motivation also have the driving mechanism to accomplish tasks. Considering the challenging tasks teachers face on daily basis, this study aims to examine how workload and motivation influence teacher performance. Using descriptive-correlational research, a survey was conducted to 45 teachers of Butuan Central Elementary School to determine the influence of their workload and level of motivation on their performance. Results showed that 62% of the participants have an ideal workload of 2,400 minutes per week and only 29% are overloaded. In terms of motivation, results showed that the participants’ level of motivation is highly observed (M=4.15). This study also looked into the relationship among work performance, length of service, education, and age. It was found that only length of service has a significant correlation with performance, although both are negatively correlated (r= -0.359, p=.015). Moreover, the relationship among performance, workload and motivation was also examined. It was found that there is no significant relationship between performance and workload (r= -0.014, p=0.928) and performance and motivation (r=0.009, p=0.954). Overall, results of this study suggest that the length of service has a significant negative relationship with performance, while teachers’ workload and work motivation have no influence on their teaching performance.